Experience of a Portuguese Center: Effectiveness of Direct-Acting Antiviral Therapy for Hepatitis C - Falcão, Fátima (2019)
Introduction: In late 2014, Portugal implemented a national program for the treatment of patients with chronic hepatitis C with directacting antiviral agents. This program has made Portugal one of the first European countries to implement a structured measure of treatment to eliminate this serious public health problem. The aim of this study was to assess the effectiveness of direct-acting antiviral therapy in the treatment of patients with chronic hepatitis C virus infection.Material and Methods: A retrospective observational study was conducted at Centro Hospitalar de Lisboa Ocidental on the national online platform from December 2014 until February 2017 and included patients with hepatitis C virus infection who underwent treatment. The primary endpoint was sustained virologic response at least 12 weeks post treatment. Data was analyzed with the SPSS 17.0 program.Results: During the study period, 820 patients completed therapy and achieved sufficient follow-up time to assess sustained virologic response with an overall response rate of 97.2% (n = 797) and a response rate of 98.0%, 99.5%, 90.9%, 95.1% and 94.2% for genotypes 1a, 1b, 2, 3 and 4, respectively. Data suggested that advanced fibrosis (F3/F4), human immunodeficiency virus co-infection and treatment failure with interferon and ribavirin were not negatively related with sustained virologic response in our population. Most patients (80.1%) completed treatment with ledipasvir/sofosbuvir ± ribavirin. The most common adverse events were fatigue and insomnia followed by headache and weight loss.Discussion: Patients predominantly had genotype 1 infection which correlates with HCV distribution in Europe, but we found a major proportion in genotype 4 which can be explained by immigration from African countries. Our patients’ ages ranging from 22 to 90 years, reflected a new approach with no upper age limit. Direct-acting antivirals regimens resulted in remarkably high SVR rates compared to interferon-based regimens, which were consistent with clinical trials data.Conclusion: Our data showed that direct-acting antiviral-based regimens are safe and have a high success rate in the treatment of patients with hepatitis C virus infection in a real-world setting.